Pseudofolliculitis barbae; current treatment options - Ogunbiyi A (Dove Medical Press, 2019)
Adebola Ogunbiyi Department of Medicine, University College Hospital, Ibadan, Oyo State, Nigeria Abstract: Pseudofolliculitis barbae (PFB) is a chronic inflammatory disorder of follicular and peri-follicular skin characterized by papules, pustules, and post-inflammatory hyperpigmentation. It occurs more frequently in men of African and Asian descent. The etiology of PFB is multifactorial. Shaving or plucking the hair precipitates the onset of an inflammatory reaction that results from the penetration of the adjacent skin by the growing sharp tips. The curved shape of the hair follicle allows for the downward curvature and penetration of the growing hair tips into the skin. The onset of the foreign body reaction leads to itching and the development of papules, pustules, and post-inflammatory hyperpigmentation, especially in the beard area although other shaved areas of the body may be affected. Keloids have also been known to develop after the onset of PFB, giving rise to extensive unsightly scars. Diagnosis is clinical. Cessation of shaving or removal of the involved hair follicles usually terminates the development of PFB. Individuals with the single nucleotide substitution in the hair follicle companion layer specific keratin gene (K6hf) have a six fold increased chance of developing PFB. Keywords: pseudofolliculitis barbae, pathogenesis, treatment